SDG-enabled decarbonisation transport pathways for mid-sized Indian cities - Darshini Mahadevia; Saumya Lathia; Chandrima Mukhopadhyay (Global Social Challenges Journal)
All international agreements recognise that sustainable development, equity and poverty alleviation are preconditions for the substantial societal and technological transformations required to limit global warming to 1.5°C. A growing body of literature indicates that while climate change undermines the progress of Sustainable Development Goals (SDGs), climate actions also pose several trade-offs with them. Climate adaptation has a largely synergistic relationship with SDGs across various socio-economic contexts. However, climate mitigation’s relationship with SDGs is far more complex. While the need to decarbonise is universal, the pathways to deliver deep decarbonisation vary across contexts and scales and are located within the local socio-economic realities besides local environmental factors. This paper argues that (1) climate mitigation measures in countries like India – with rising income inequality and high social diversity in caste, religion and region – need a tailored assessment approach, (2) carefully mediating climate mitigation measures – like deep decarbonisation – at the local level is crucial to enable transformative change required to meet the Paris Agreement and the UN Agenda 2030, (3) enabling ‘just’ deep decarbonisation or SDG-enabled decarbonisation at the local level requires addressing unmet needs of the vulnerable population even at the cost of increased emissions, and (4) sector-specific decarbonisation strategies at the national level must be translated into the local area’s social, economic, environmental and institutional realities. This paper grounds this approach using the example of the transport sector and applies it in a mid-sized city of India, Udaipur, to illustrate the argument.